Concentrations of angiogenic factors in follicular fluid and oocyte-cumulus complex culture medium from women undergoing in vitro fertilization: Association with oocyte maturity and fertilization - Malamitsi-Puchner, A.; Sarandakou, A.; Baka, S.G.; Tziotis, J.; Rizos, D.; Hassiakos, D.; Creatsas, G. (Fertility and Sterility, 2001)
Objective: To determine the concentration of angiogenic factors (vascular endothelial growth factor [VEGF], basic fibroblast growth factor [bFGF], and angiogenin) in the follicular fluid (FF) and oocyte-cumulus complex culture medium (CM) of women undergoing IVF and to investigate the association of the concentrations with the maturity and fertilization of the oocyte. Design: Prospective study. Setting: Academic tertiary-care institution. Patient(s): IVF patients with unexplained or tubal factor infertility.Intervention(s): Analysis of VEGF, bFGF, and angiogenin FF and CM concentrations. Main Outcome Measure(s): Oocyte maturity and fertilization and FF and CM angiogenic factor concentrations.Result(s): VEGF, bFGF, and angiogenin were determined in FF and CM. FF angiogenin concentrations were significantly higher when the oocyte was mature versus immature. CM VEGF concentrations were significantly higher when the oocyte was nonfertilized versus fertilized. Positive correlations were observed between angiogenic factors in CM. Conclusion(s): VEGF, bFGF, and angiogenin (determined for the first time) are secreted in the FF and CM. Elevated CM VEGF concentrations, probably implying oocyte-cumulus complex hypoxia, are negatively associated with oocyte fertilization. Elevated FF angiogenin concentrations are positively associated with oocyte maturity, possibly indicating angiogenin's biological role beyond neovascularization. Copyright © 2001 American Society for Reproductive Medicine.
Keywords: Angiogenin; Basic fibroblast growth factor; Fertilization; Follicular fluid; Oocyte maturity; Oocyte-cumulus complex; Vascular endothelial growth factor